Α‐Substitution Effects on the Ease of S→N‐Acyl Transfer in Aminothioesters. (24th April 2013) - El‐Gendy, Bahaa El‐Dien M.; Ghazvini Zadeh, Ebrahim H.; Sotuyo, Ania C.; Pillai, Girinath G.; Katritzky, Alan R.
<x xml:space="preserve">Abstract</x> In S‐acylcysteines and homocysteines, the efficacy and rate of S→N‐acyl transfer (5 and 6 cyclic TSs) vary with the size of S‐acyl group. Conformational and quantum chemical calculations indicate that the spatial distance, b(N‐C), between the terminal amine and the thioester carbon is shortened by α‐C(O)X (X = OH, OMe, NH2) substituents.